PENGARUHKOMPENSASIFINANSIALDANSEMANGAT KERJA TERHADAP KINERJA KARYAWAN PADAKOPERASI SIMPAN PINJAM â€œMUHAMMADIYAHDI MARTAPURAâ€ KABUPATEN BANJAR - Abdul Kadir (RJABM (Research Journal of Accounting and Business Management), 2021)
Abstract: The purpose of this study was to determine the effect of financial compensation and work morale on employee performance at the Savings and Loans Cooperative "Muhammadiyah in Martapura" Banjar Regency. simultaneously, partially and dominantly. This study uses an analytical survey research method with a cross sectional approach. The population in this study were 35 people. The sample in this study used a total sampling technique of 35 people in 2020. Data collection techniques used questionnaires, documentation, interviews and observations. The data analysis technique uses regression analysis with computerized assistance and the SPSS Version 25 program. The results of the study can be concluded that financial allowances and work morale have a simultaneous influence on employee performance at the Savings and Loans Cooperative "Muhammadiyah in Martapura" Banjar Regency. Financial allowances and morale have a partial effect on employee performance at the Savings and Loans Cooperative "Muhammadiyah in Martapura" Banjar Regency. Morale (X2) is the variable that has the most dominant influence on employee performance at the Savings and Loan Cooperative "Muhammadiyah in Martapura" RegencyÂ Kata Kunci : tunjangan finansial, semangat kerja, kinerjaÂ